2019
DOI: 10.1001/jamapediatrics.2018.4602
|View full text |Cite
|
Sign up to set email alerts
|

The Need for an Intervention to Prevent Sports Injuries

Abstract: Although 1.35 million children visit emergency departments for sports-related injuries each year in the United States, athletic bodies lack a systematic approach for monitoring injury risk and adopting interventions to curtail injuries. 1 Rather than using randomized clinical trials or other evidence-based approaches to evaluate interventions, the decision-making process for adopting interventions is characterized by protracted debates that overweigh subjective factors, such as how sports have traditionally be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Understanding the mechanics that produce these injuries after impact can inform the type of protective gear needed for athletes participating in different sports. [28][29][30][31] The prevalence of TSCI varied between sporting activities, with water sports and contact sports resulting in the highest prevalence of TSCI within this cohort. Previous studies have identified diving as the primary source of water sports-related injury, highlighting how the lack of protective equipment in this activity and related sports leaves patients more vulnerable to devastating neurological injury.…”
Section: Discussionmentioning
confidence: 86%
“…Understanding the mechanics that produce these injuries after impact can inform the type of protective gear needed for athletes participating in different sports. [28][29][30][31] The prevalence of TSCI varied between sporting activities, with water sports and contact sports resulting in the highest prevalence of TSCI within this cohort. Previous studies have identified diving as the primary source of water sports-related injury, highlighting how the lack of protective equipment in this activity and related sports leaves patients more vulnerable to devastating neurological injury.…”
Section: Discussionmentioning
confidence: 86%
“…Use of text-based health care communications is likely to continue to grow, evidenced by both traditional health care institutions, such as BMC, and the growing sector of digital-first care institutions, such as Firefly and Ginger, which often rely on text-based messaging with a health coach as a first-line triage point before patients receive clinician-based care . Additionally, while AI tools have been discussed as a means for triaging and responding to patient text-based requests, prior work has shown that AI tools can perpetuate underlying inequalities in the data that algorithms were trained on . Understanding and correcting existing disparities in care team response to patient messages will be vital for increasing equity in care today and the algorithms of the future.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of clear and unambiguous evidence about what warmup activities are effective, it is unlikely that many non-professional athletes consistently engage in warmup activities that will be optimally effective for injury prevention. This highlights the need to develop, disseminate and implement injury preventing warmups [42]. Moreover, previous studies have shown that initial benefits of a neuromuscular warmup routine decline if adherence wanes over time [43].…”
Section: Table 6 Effectiveness-knee Injuries (General)mentioning
confidence: 99%